Pathological Findings Associated With SARS-CoV-2 on Postmortem Core Biopsies: Correlation With Clinical Presentation and Disease Course - Ramos-Rincon, Jose-Manuel; Herrera-García, Cristian; Silva-Ortega, Sandra; Portilla-Tamarit, Julia; Alenda, Cristina; Jaime-Sanchez, Francisco-Angel; Arenas-Jiménez, Juan; Fornés-Riera, Francisca-Eugenia; Scholz, Alexander; Escribano, Isabel; Pedrero-Castillo, Víctor; Muñoz-Miguelsanz, Carlos; et al. (Frontiers in Medicine, 2022)
Background: Autopsies can shed light on the pathogenesis of new and emerging diseases. Aim: To describe postmortem biopsy findings of the lung, heart, and liver in decedents with COVID-19. Material: Cross-sectional study of postmortem needle core biopsies in patients who died with virologically confirmed COVID-19. Histopathological analyses were performed, and clinical data and patient course evaluated. Results: Postmortem chest biopsies were performed in 71 decedents with a median age of 81 years (range 52 to 97); 47 (65.3%) were men. The median interval from symptoms onset to death was 17.5 days (range 1 to 84). Samples of lung (n=62, 87.3%), heart (n=48, 67.6%) and liver (n=39, 54.9%) were obtained. Fifty-one lung samples (82.3%) were abnormal: 19 (30.6%) showed proliferative diffuse alveolar damage (DAD), 12 (19.4%) due to exudative DAD, and 10 (16.1%) exhibited proliferative plus exudative DAD. Of the 46 lung samples tested for SARS-CoV-19 by RT-PCR, 39 (84.8%) were positive. DAD was associated with premortem values of lactate dehydrogenase of 400 U/L or higher (adjusted odds ratio [AOR] 21.73; 95% confidence interval [CI] 3.22-146) and treatment with tocilizumab (AOR 6.91; 95% CI 1.14-41.7). Proliferative DAD was associated with an onset-to-death interval of over 15 days (AOR 7.85, 95% CI 1.29-47.80). Twenty-three of the 48 (47.9%) heart samples were abnormal: all 23 showed fiber hypertrophy, while 9 (18.8%) presented fibrosis. Of the liver samples, 29/39 (74.4%) were abnormal, due to steatosis (n=12, 30.8%), cholestasis (n=6, 15.4%) and lobular central necrosis (n=5, 12.8%). Conclusion: Proliferative DAD was the main finding on postmortem lung biopsy in people who died from COVID-19; this finding was related to a longer disease course. Changes in the liver and heart were common.